Embracing Nature in the Built Environment: Evaluation of Biophilic Design Patterns in Selected Resorts - Abraham, Ajijolaoluwa Oluwasemilore; Oluwatayo, Adedapo A.; Nduka, Dike M. (Journal of A Sustainable Global South; Vol 7 No 2 (2023): August 2023, 2023)
The integration of natural elements into the built environment, commonly referred to as biophilic design, has garnered interest due to its capacity to improve well-being and foster sustainable lifestyles. Resorts, which serve as temporary retreats for individuals seeking relaxation and leisure, offer a range of amenities and the opportunity to engage with nature. This paper aims to investigate the implementation of biophilic design patterns within selected resorts. Given its rich heritage and abundant natural resources, Ibadan, Nigeria was selected as the study location for this study. The research employed a quantitative methodology, employing convenience sampling to ensure a representative sample from the population. Questionnaires were distributed using a census sampling technique. The results of this study demonstrate a substantial implementation of biophilic design strategies in the chosen resorts. It is strongly advised to incorporate biophilic design strategies right from the inception of the design process, rather than considering them as an afterthought.